A mermaid's tale [videorecording (DVD)] - O'Connell, Jerry, 1974-; Bostwick, Barry; Carmichael, Caitlin, 2004-; Stafford, Nancy, 1954- (Lionsgate, 2017)
When a twelve-year-old girl befriends a quirky teenage mermaid who's anything but mythical, their friendship could heal an age-old feud between humans and sea people. Jerry O'Connell and Barry Bostwick bring to life this family-friendly saga of a young girl's playful friendship with a teenage mermaid.